The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s12993-017-0126-3
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in avoidance behavior after perceiving potential risk in mice

Abstract: BackgroundSex has been considered as a potential factor regulating individual behaviors in different contexts. Recently, findings on sex differences in the neuroendocrine circuit have expanded due to exact measurements and control of neuronal activity, while findings on sex differences in behavioral phenotypes are limited. One efficient way to determine the miscellaneous aspects of a sexually different behavior is to segment it into a set of simpler responses induced by discrete scenes.MethodsIn the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 46 publications
4
13
0
Order By: Relevance
“…Similarly, other studies performed at some points of the beginning-middle [ZT2-ZT5 (Võikar et al, 2001) and ZT3.5-6.5 (Huang et al, 2017)] or middle-end period of the light phase [ZT5-10 (Salari and Amani, 2017)] revealed no significant differences between male and female mice in parameters tested in the light-dark test. These findings were also confirmed by some other studies that did not specify the exact period of the light phase when the experiments were performed (Ding et al, 2014;Tucker et al, 2017;Yokota et al, 2017). During the dark phase, Barreto-Estrada et al (2004) demonstrated that there were no sex differences in the light-dark transition.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Similarly, other studies performed at some points of the beginning-middle [ZT2-ZT5 (Võikar et al, 2001) and ZT3.5-6.5 (Huang et al, 2017)] or middle-end period of the light phase [ZT5-10 (Salari and Amani, 2017)] revealed no significant differences between male and female mice in parameters tested in the light-dark test. These findings were also confirmed by some other studies that did not specify the exact period of the light phase when the experiments were performed (Ding et al, 2014;Tucker et al, 2017;Yokota et al, 2017). During the dark phase, Barreto-Estrada et al (2004) demonstrated that there were no sex differences in the light-dark transition.…”
Section: Discussionsupporting
confidence: 76%
“…In addition to the above, most of the studies have suggested that there are no sex differences in PA memory in mice tested during the light (Rayburn et al, 2001;Rizk et al, 2005;Benice et al, 2006;Fernandes-Santos et al, 2012;Balsevich et al, 2014;Zanos et al, 2015;Dachtler et al, 2016;Maurice et al, 2016;Jardim et al, 2017;Adelöf et al, 2019) and dark phase of the 12/12 cycle (Podhorna et al, 2002;Xu et al, 2011;Parra et al, 2013). In contrast, Xu et al (2013) found that female ICR mice tested at ZT2-7 showed shorter latency than males on the retention trial in the step-down PA test, while Yokota et al (2017) found that female C57BL/6N mice displayed significantly longer latency to enter into the dark chamber of the step-through PA task than the male counterparts. The data from the present study showed that female mice performed significantly better than males at the ZT0-2.5 while at the ZT9.5-12 there were no sex differences in the PA latency.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The mice were handled for 5 consecutive days prior to the commencement of contextual fear conditioning. The mice were trained and tested in conditioning chambers (17.5 × 17.5 × 15 cm; O’HARA & Co., Ltd., Tokyo, Japan) that had a stainless-steel grid floor through which the footshock could be delivered [ 15 , 48 , 60 , 61 , 78 , 82 , 83 ]. Training consisted of placing the mice in the chamber and delivering an unsignaled footshock (2 s duration, 0.4 mA) 148 s later.…”
Section: Methodsmentioning
confidence: 99%